Answer:
B. All real numbers
Step-by-step explanation:
2(x + 1) = 2x + 2
Distribute the 2 inside the parenthesis.
2x + 2 = 2x + 2
Since the two expressions are equal and will stay equal with any value, the answer to this question is All real numbers.
Example:
2(x + 1) = 2x + 2
2(5 + 1) = 2(5) + 2
2(6) = 10 + 2
12 = 12
2(x + 1) = 2x + 2
2(150 + 1) = 2(150) + 2
2(151) = 300 + 2
302 = 302
The expression is equal for any value put in x.
Answer:
a = 3
Step-by-step explanation:
Factor both expressions
x² - x - 6
Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (- 1)
The factors are - 3 and + 2 , since
- 3 × 2 = - 6 and - 3 + 2 = - 1 , thus
x² - x - 6 = (x - 3)(x + 2)
-----------------------------------
x² + 3x - 18
consider factors of constant term (- 18) which sum to give the coefficient of the x- term (+ 3)
The factors are + 6 and - 3 , since
6 × - 3 = - 18 and 6 - 3 = + 3 , thus
x² + 3x - 18 = (x + 6)(x - 3)
Both expressions have a common factor of (x - 3)
Compare with (x - a ), then a = 3
Step-by-step explanation:
hope this helped you :)) !!
Answer:
3x+0.3=3.3.
\ /
We move all terms to the left:
3x+0.3-(3.3.)=0
We add all the numbers together, and all the variables
3x+0.3-0=0
We add all the numbers together, and all the variables
3x+0.3=0
We move all terms containing x to the left, all other terms to the right
3x=-0.3
x=-0.3/3
x=-0.3/3
/ \
*eliza*
Answer:
B
Step-by-step explanation: